An examination of the antibacterial, antifungal, anti-Giardial and anticancer properties of Kigelia africana fruit extracts - A, Arkhipov; J, Sirdaarta; P, Rayan; PA, McDonnell; IE, Cock (Pharmacognosy Communications)
Background: Kigelia africana is a common component of the pharmacopeia’s of multiple African groupings which inhabit the areas in which it grows. Amongst these groups there is a myriad of medicinal uses in the treatment of a wide variety of bacterial, fungal and protozoal infections, as well as in the treatment of cancers. This study was undertaken to test K. africana fruit extracts for the ability to inhibit microbial and cancer cell growth, and thus to validate traditional African medicinal usage of this plant in treating a variety of diseases. Materials and Methods: K. africana fruit powder was extracted and tested for antimicrobial activity using modified disc diffusion and MIC methods. Inhibitory activity against the gastrointestinal protozoal parasite Giardia duodenalis and against CaCo2 and HeLa cancer cell lines was evaluated using colorimetric cell proliferation assays. Toxicity was evaluated using an Artemia franciscana nauplii bioassay. Results: The methanol, water and ethyl acetate K. africana fruit extracts displayed potent antibacterial activity. The methanol and water extracts displayed the broadest specificity, inhibiting the growth of 12 of the 18 bacteria tested (67 %) and 11 of the 18 bacteria tested (61 %) respectively. The ethyl acetate extract also displayed antibacterial activity, inhibiting the growth of 4 (22 %) of the 18 bacteria tested. These extracts were approximately equally effective against Gram-positive and Gram-negative bacteria, generally inhibiting the growth of 60–70 % of the bacteria tested. The methanol, water and ethyl acetate extracts also displayed broad spectrum antifungal activity, each inhibiting the growth of 3 of the 4 fungal species tested (75 %), including an ampicillin strain of A. niger. The methanol, water and ethyl acetate extracts also inhibited between 55 and 70 % of the growth of the gastrointestinal parasite Giardia duodenalis. These extracts also proved effective at blocking the proliferation of the colorectal cancer cell line CaCo2 to between 37 and 55 % of the untreated cell growth. The methanol extract also inhibited HeLa cervical cancer cell growth, albeit to a lesser extent (81 % of the untreated control growth), whilst the chloroform and hexane extracts stimulated HeLa cell proliferation. With the exception of the water extract, all extracts were non-toxic or of low toxicity. Conclusion: These studies validate traditional African therapeutic usage of K. africana in the treatment of several bacterial, fungal and protozoal illnesses and some cancers.
Keywords: Antibacterial activity; Sausage tree; Giardia duodenalis; Anti-proliferative activity; Anti-cancer activity; Artemia; Toxicity